The problem of the electronic contract as evidence in civil relations - Dashkovets, A.V. (ХНУ ім. В. Н. Каразіна, 2012)
The paper considers the problem of e-contract as evidence in legal proceedings. It addresses the main aspects of legal regulations both in international law and in various national legal systems.
В статье рассматривается проблема электронного договора, как доказательства в судебном процессе. Затрагиваются основные аспекты правового регулирования, как в области международного права, так и в различных национальных системах права.
Keywords: E-commerce; electronic contract; digital signature; validity